Comparison of patient-controlled analgesia versus continuous infusion of tramadol in post-cesarean section pain management - Demirel, Ismail; Ozer, Ayse Belin; Atilgan, Remzi; Kavak, Burcin Salih; Unlu, Serap; Bayar, Mustafa Kemal; Sapmaz, Ekrem (Wiley, 2014)
AimTo evaluate and compare analgesic efficacy, drug consumption and patient satisfaction with the i.v. patient-controlled and continuous infusion modes of administration of tramadol. MethodsA total of 40 pregnant women in American Society of Anesthesiologists physical status classification system risk classes I-II scheduled for cesarean section were randomized into two groups to receive treatment in single-blind fashion. Patients in both groups received tramadol as an i.v. infusion 15min before the end of surgery under general anesthesia for cesarean section. In the post-anesthesia care unit, the 20 patients allocated to group I were given i.v. tramadol in patient-controlled anesthesia (PCA), while the 20 other patients assigned to group II received it as a continuous infusion. Pain visual analog scores (VAS), mean arterial pressure (MAP), heart rate, total tramadol consumption, sedation scores, side-effects (nausea/vomiting) and patient satisfaction were evaluated seven times in the course of the first postoperative 24h. The Mann-Whitney U-test and Friedman's anova were used for the statistical treatment of data. ResultsVAS, sedation scores and nausea/vomiting scores were similar in both groups (P>0.05). The 24-h tramadol consumption was significantly lower in group I (420.1566.58mg) than in group II (494.00 +/- 29.45mg), while patient satisfaction was significantly higher in group I (P<0.05). ConclusionWhile tramadol administration by either of the methods used may ensure efficient early postoperative anesthesia in cesarean section patients, i.v. PCA may be preferred because of the lower drug consumption and higher patient satisfaction associated with it.
Keywords: analgesia; cesarean section; infusions; intravenous; patient-controlled; tramadol